The Implementation of Individual Counseling Using Reality Therapy to Enhance Self-Identity of Vocational High School Students - Helvy Hilyatul Aulia; Fauzi Nur Ilahi; Sabrina Dachmiati (Multidisciplinary Journals, 2025)
Self-identity is a vital aspect of adolescent development that does not automatically mature with age, but rather requires a deep reflective process and sufficient psychological support. School-based counseling services, particularly individual counseling with a reality therapy approach, can serve as a restorative space for students experiencing identity confusion. This study aims to describe the process and outcomes of applying reality therapy techniques in helping a vocational high school student shape a clearer sense of self. Using a qualitative case study design, data were collected through observation, in-depth interviews, and documentation involving one tenth-grade student at SMK Negeri 18 Jakarta. The findings reveal that individual counseling based on reality therapy helps the counselee recognize psychological needs, re-evaluate life choices, and build confidence in engaging with social roles. The counseling process emerged as a transformative experience that touched the student's personal and emotional dimensions, showing tangible improvements in behavior, social participation, and self-perception. This study recommends wider implementation of similar counseling approaches, supported by school policies that prioritize students’ long-term psychological growth.